Sequenciamento e caracterização do genoma da cepa ph8 de leishmania amazonensis com ênfase em fatores de virulência possivelmente envolvidos no estabelecimento e visceralização da infecção - Wanessa Moreira Goes (2023)
Leishmania amazonensis is one of the etiologic agents of cutaneous leishmaniasis, a disease with 21,000 cases/year in Brazil. Different molecules of the parasite have already been studied because they play a crucial role in the invasion and establishment of infection in the mammalian host, including the visceralization of amastigotes, which contributes to the increase in the pathogenesis of leishmaniasis. To deepen the studies on these virulence factors, it is necessary to obtain complete genomes with adequate annotations of different strains and isolates of L. amazonensis. Despite having been described in 2013, the genome of this parasite has not yet been completely sequenced, assembled and annotated. In the present work, we report the sequencing and assembly of the genome of the PH8 strain of L. amazonensis using a strategy based on the combination of long coverage reads obtained on the PacBio platform, reads from Illumina with short coverage and also synteny data with the Leishmania mexicana genome. The initial contigs were generated using only the PacBio reads and the Canu assembler, and the IPA pipeline was used to remove redundant contigs. The scaffolding step was performed using SSPACE and gap filling with GapFiller, based on Illumina paired-end short reads. Finally, the assembly was polished using Pilon, and the scaffolds were sorted based on L. mexicana chromosomes using Abacas. The final assembly, composed of 34 pseudochromosomes and 42 unincorporated scaffolds, represents a genome of ~32 Mb, plus the maxicircle sequence of 18.1 kb. Then, the occurrence of aneuploidies for several chromosomes of the PH8 strain and the presence of gene expansions related to genes that encode virulence factors such as amastins, GP63 and protein kinases were analyzed. Repetitive sequences were described for the first time revealing the predominance of retroelements and DNA transposons. The annotation of the gene content of L. amazonensis was conducted using two approaches: ab initio and based on transferring the annotation of a total of 8,2317 genes present in the genome of L. mexicana. Of these, 7999 are protein coding genes and 318 of them are classified as pseudogenes. Several multigene families that encode virulence factors, such as A2 proteins, amastins, GP63 metalloproteins, phosphatases and cysteine proteases, were identified and compared with their annotation in the genome of other trypanosomatid species. The genome of the PH8 strain has 29 genes that encode all four subclasses of amastins (α, β, γ and δ), 5 genes that encode A2 antigens, 9 genes that encode the GP63 metalloprotease and 76 cysteine proteases genes. As they were recently recognized as essential virulence factors for the establishment of the disease and progression of the infection, 14 genes were also identified that encode proteins involved in the iron and heme metabolism of the parasite, which were compared with the gene repertoire related to these pathways present in other trypanosomatids. Based on this genomic study and on recent studies by our group describing new genome editing methods, deepening the knowledge about these and other virulence factors and, as a consequence, accelerating the development of new strategies control of infection caused by L. amazonensis.